ANALISIS SPASIAL KETERSEDIAAN AIR UNTUK TANAMAN PADI DI KOTA BENGKULU - Siska Siska; Helfia Edial (JURNAL BUANA, 2021)
The purpose of this study was to determine the availability and distribution of water for rice crops and the suitability of land to water availability in Bengkulu City. This type of research is quantitative descriptive using secondary data, namely the monthly average rainfall and air temperature for 30 years and then processed using the Thornwaite-Matter method. The results of this study found that the availability of water for rice plants in Bengkulu City every month was dominated by a surplus condition, a surplus condition occurred in each region in Bengkulu City in January-June, August, and October-December. The balance situation occurred in July, in Teluk Segara District, Serut River, Muara Bangkahulu, Singaran Pati, Gading Cempaka, as wide as a small part of Kampung Melayu. Meanwhile, the deficit situation occurred in July and September in Ratu Agung, Singaran Pati, Gading Cempaka, and most of Muara Bangkahulu Districts. Meanwhile, the availability of water for rice plants in Bengkulu City is in accordance with the land designation for this type of rice plant.